British Dietetic Association systematic review of systematic reviews and evidence‐based practice guidelines for the use of probiotics in the management of irritable bowel syndrome in adults (2016 update). Issue 5 (6th June 2016) - McKenzie, Y. A.; Thompson, J.; Gulia, P.; Lomer, M. C. E.; ,
Abstract: Background: Probiotics are often taken by individuals with irritable bowel syndrome (IBS). Which products are effective is unclear, despite an increasing research base. This project will systematically review which strain‐ and dose‐ specific probiotics can be recommended to adults with IBS to improve symptoms and quality of life (QoL). It is part of a broader systematic review to update British Dietetic Association guidelines for the dietary management of IBS in adults. Methods: CINAHL, Cochrane, Embase, Medline, Scopus and Web of Science were searched for systematic reviews (SRs) of randomised controlled trial (RCT)s recruiting adults with IBS comparing probiotic intervention with placebo. AMSTAR, risk of bias and diet bias tools were used to appraise methodological quality. Symptom and QoL data were appraised to develop probiotic‐specific evidence statements on clinically meaningful and marginal outcomes in various settings, graded clinical practice recommendations and practical considerations. Results: Nine systematic reviews and 35 RCTs were included (3406 participants) using 29 dose‐specific probiotic formulations. None of the RCTs were at low risk of bias. Twelve out of 29 probiotics (41%) showed no symptom or QoL benefits. Evidence indicated that no strain or dose specific probiotic was consistently effective to improve any IBS symptoms or QoL. Two general clinical practice recommendations were made. Conclusions: Symptom outcomes for dose‐specific probiotics were heterogeneous. Specific probiotic recommendations for IBS management in adults were not possible at this time. More data from high‐quality RCTs treating specific symptom profiles are needed to support probiotic therapy in the management of IBS.